2020
DOI: 10.1111/jth.15105
|View full text |Cite
|
Sign up to set email alerts
|

Placenta‐mediated complications: Nucleosomes and free DNA concentrations differ depending on subtypes

Abstract: Background: Placenta-mediated pregnancy complications generate short-and longterm adverse medical outcomes for both the mother and the fetus. Nucleosomes and free DNA (fDNA) have been described in patients suffering from a wide range of inflammatory conditions. Objective: The objective of our study was to compare nucleosomes and fDNA circulating levels during pregnancy and particularly in women developing a placenta-mediated complication according to the subtype (preeclampsia or intrauterine growth restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…Several studies, including our data, 4 have shown that plasma nucleosomes and cell-free DNA (cfDNA) increased during pregnancy, and that their levels were even higher in women with PMPCs, particularly in PE. 5,6 Nucleosomes are key components of neutrophil extracellular traps (NETs) and are released by neutrophil activation, a process called NETosis.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Several studies, including our data, 4 have shown that plasma nucleosomes and cell-free DNA (cfDNA) increased during pregnancy, and that their levels were even higher in women with PMPCs, particularly in PE. 5,6 Nucleosomes are key components of neutrophil extracellular traps (NETs) and are released by neutrophil activation, a process called NETosis.…”
Section: Introductionsupporting
confidence: 53%
“…It was a pilot monocentric study with a small sample size, mainly of women developing PE or IUGR, based on our recruitment capacities in the main "Grosspath" study (clinicaltrials.gov identifier: NCT 01736826). 4 Placenta-mediated complications often present as a clinical emergency with women under stress, making inclusion of these patients complicated. In addition, due to the strong commitment of women in the normal pregnancy longitudinal follow-up group, with a significant number of visits and blood tests required, it was difficult to increase inclusion numbers.…”
Section: Discussionmentioning
confidence: 99%
“…49 For example, in preeclampsia, incomplete endovascular trophoblast invasion with the reduced remodeling of uterine arteries leads to placental hypoperfusion and cytokine production, and increased nucleosome and cell-free DNA in plasma activate coagulation. 50 51 Different from other thrombotic DIC, the clinical characteristics of non–bleeding-caused obstetrical DIC are often organ dysfunction associated with bleeding. 52 The consumption of coagulation factors following activated coagulation, especially the depletion of fibrinogen, is the crucial point in the development of impaired hemostasis.…”
Section: Thrombosis-type Disseminated Intravascular Coagulationmentioning
confidence: 99%
“… 35 , 36 The underlying pathologies responsible for such quantitative changes has not been fully elucidated but has been suspected to be related to increased placental cell death or apoptosis. 35 , 37 , 38 Circulating fetal DNA levels may therefore be reflective of placental health. Because massively parallel sequencing‐based methods mainly report DNA quantities as a fraction, researchers also studied if aberrant fetal DNA fractions were associated with pregnancy‐related or maternal conditions.…”
Section: Quantities and Abundancementioning
confidence: 99%